Circular RNA Circ_0013958 Functions as a Tumor Promoter in Ovarian Cancer by Regulating miR-637/PLXNB2 Axis - Liang, Yanfei; Meng, Kaiyi; Qiu, Rui (Frontiers in Genetics, 2021)
Background: Circular RNAs (circRNAs) have emerged as important regulators in diverse human malignancies, including ovarian cancer (OC). This study was performed to explore the function and regulatory mechanism underlying circ_0013958 in OC progression. Methods: Quantitative real-time polymerase chain reaction (qRT-PCR) or Western blot assay was applied to examine the expression of circ_0013958, microRNA-637 (miR-637), and Plexin B2 (PLXNB2). The target relationship between miR-637 and circ_0013958 or PLXNB2 was verified by dual-luciferase reporter assay or RNA immunoprecipitation (RIP) assay. Cell Counting Kit-8 (CCK-8) and colony formation assays were employed to detect cell viability and clonogenicity ability, respectively. Cell migration and invasion were analyzed by Transwell assay. Cell apoptosis was monitored by flow cytometry. The role of circ_0013958 in vivo was determined by xenograft tumor assay. Results: Circ_0013958 and PLXNB2 were upregulated, while miR-637 was downregulated in OC tissues and cells. Circ_0013958 acted as a sponge for miR-637 to regulate the expression of PLXNB2 in OC cells. The repression effects of circ_0013958 knockdown on cell proliferation, migration, invasion, and apoptosis in OC cells were partly attenuated by the miR-637 inhibitor. And miR-637 targeted PLXNB2 to suppress OC cell proliferation, migration, and invasion. Moreover, circ_0013958 silencing blocked OC tumor growth in vivo. Conclusion: Circ_0013958 knockdown impeded OC development through modulating the miR-637/PLXNB2 axis, highlighting a therapeutic target for OC.